2017
DOI: 10.18632/oncotarget.22607
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of N’-methyl-2-pyridone-5-carboxamide and lysophosphatidylcholine 16:0 in the serum of patients with intrahepatic cholangiocarcinoma, and the correlation with recurrence-free survival

Abstract: We searched for metabolic biomarkers that may predict the prognosis of patients with intrahepatic cholangiocarcinoma (IHCC). To this end, a total of 237 serum samples were obtained from IHCC patients (n = 87) and healthy controls (n = 150), and serum metabolites were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Two stratified algorithms were used to select the metabolites, the levels of which predicted the prognosis of IHCC patients. We performed MS/MS and multiple-reaction-monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Furthermore, LysoPC can inhibit cholangiocyte apoptosis by inducing COX-2 expression via a Raf-1-dependent mechanism, and such anti-apoptotic effects might be important in biliary tract carcinogenesis in patients with compromised pancreaticobiliary ductal junctions [ 46 ]. Similar to other types of cancer, we found a reduced level of LysoPC in the serum of BTC patients [ 47 ], as well as significantly decreased levels of LysoPC in the bile of these patients compared with those with benign biliary tract disease [ 10 ]. These findings strongly imply that LysoPC may be useful for BTC diagnosis and prognosis [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, LysoPC can inhibit cholangiocyte apoptosis by inducing COX-2 expression via a Raf-1-dependent mechanism, and such anti-apoptotic effects might be important in biliary tract carcinogenesis in patients with compromised pancreaticobiliary ductal junctions [ 46 ]. Similar to other types of cancer, we found a reduced level of LysoPC in the serum of BTC patients [ 47 ], as well as significantly decreased levels of LysoPC in the bile of these patients compared with those with benign biliary tract disease [ 10 ]. These findings strongly imply that LysoPC may be useful for BTC diagnosis and prognosis [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 71%
“…Similar to other types of cancer, we found a reduced level of LysoPC in the serum of BTC patients [ 47 ], as well as significantly decreased levels of LysoPC in the bile of these patients compared with those with benign biliary tract disease [ 10 ]. These findings strongly imply that LysoPC may be useful for BTC diagnosis and prognosis [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 71%
“…In the context of cancer research decreased levels of certain LPCs were identified as potential biomarkers in colorectal cancer [ 144 , 145 , 146 ], hepatocellular carcinoma [ 147 ], ovarian cancer [ 148 , 149 ], cholangiocarcinoma [ 150 ], pancreatic and biliary tract cancer [ 151 ] as well as cervical cancer [ 152 ]. Of particular interest, LPC levels proved to correctly predict the recurrence of prostate cancer after surgery [ 153 ].…”
Section: Future Directions Of Lpc As a Biomarkermentioning
confidence: 99%
“…Pyridones and methyl-nicotinamide are measured in clinical settings to identify vitamin B3 deficiencies [ 48 , 49 ] and in metabolomics as they associate with increased NAD consumption [ 50 , 51 ] and cellular dysfunctions in tissues [ 51 , 52 , 53 , 54 , 55 ]. Unfortunately, over the years the nomenclature used to describe the pyridone’s nature thus characterized has been somewhat unsystematic and exquisitely confusing (e.g., [ 5 , 11 , 56 ]).…”
Section: Discussionmentioning
confidence: 99%